Peran Kemenko Perekonomian dalam Pemberdayaan UMKM Berbasis Prinsip Ekonomi Pancasila: The Role of the Coordinating Ministry for the Economy in Empowering MSMEs Based on Pancasila Economic Principles - Salsabila Oktaviana; Maya Balqis Danu Kundono; Siti Kusnul Khotimah; Rasyid Abdillah Ridho (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
This study aims to analyze the role of the Coordinating Ministry for Economic Affairs (Kemenko Perekonomian) in empowering Micro, Small, and Medium Enterprises (MSMEs) based on the principles of Pancasila economics. MSMEs are the backbone of the Indonesian economy, but still face limited access to financing, technology, and markets. The principles of Pancasila economics emphasize social justice, economic democracy, and shared prosperity, making them relevant as a basis for MSME empowerment. The research method uses a qualitative-descriptive approach through literature studies, policy analysis, and in-depth interviews with stakeholders. The results show that the Coordinating Ministry for Economic Affairs plays a strategic role in cross-ministerial coordination to provide inclusive financing access, MSME digitalization, and strengthening the entrepreneurial ecosystem. However, obstacles were identified in the form of complex bureaucracy, suboptimal inter-agency coordination, and limited monitoring. The study's conclusion confirms that strengthening the role of the Coordinating Ministry for Economic Affairs is crucial to ensure MSME empowerment aligns with Pancasila values. This study provides academic contributions by expanding the literature on Pancasila economics and the government's coordinating role, as well as practical contributions in the form of policy recommendations for inclusive and sustainable MSME empowerment.